Elements of a Digital Urbanisation Strategy for Türkiye: Evidence from Psychometric Testing - Fatih Eren; Kübra Çay (Social Sciences)
The research aims to explore the key components of an ideal grassroots-based digital urbanisation strategy for Türkiye. This exploration seeks to shed light on the most effective digital urbanisation strategies for Türkiye. Data were collected through a literature review, in-depth interviews with experts and psychometric testing methods, and analysed through psychometric assessment and document content analysis. The research indicates that an ideal grassroots-based digital urbanism strategy for Türkiye should focus on people, use technology to ease everyday activities, maintain personal data privacy, be adaptable, encourage diversity, provide freedom and opportunities, protect the city’s heritage, and strive for sustainability. By aligning with these essential elements, revisiting the national strategy documents crafted by the Turkish authorities to enhance the digitalisation process will allow future action plans to be grounded in a more practical framework.